Halogen bonding in water results in enhanced anion recognition in acyclic and rotaxane hosts. - Langton, M; Robinson, S; Marques, I; Félix, V; Beer, P (Nature Publishing Group, 2014)
Halogen bonding (XB), the attractive interaction between an electron-deficient halogen atom and a Lewis base, has undergone a dramatic development as an intermolecular force analogous to hydrogen bonding (HB). However, its utilization in the solution phase remains underdeveloped. Furthermore, the design of receptors capable of strong and selective recognition of anions in water remains a significant challenge. Here we demonstrate the superiority of halogen bonding over hydrogen bonding for strong anion binding in water, to the extent that halide recognition by a simple acyclic mono-charged receptor is achievable. Quantification of iodide binding by rotaxane hosts reveals the strong binding by the XB-rotaxane is driven exclusively by favourable enthalpic contributions arising from the halogen-bonding interactions, whereas weaker association with the HB-rotaxanes is entropically driven. These observations demonstrate the unique nature of halogen bonding in water as a strong alternative interaction to the ubiquitous hydrogen bonding in molecular recognition and assembly.